Transferência de massa em reator eletroquímico de carbono vítreo reticulado - Costa, Pedro Henrique de Britto (2010)
In this work, the electrodeposition of toxic metals, copper and zinc in this case, onreticulated vitreous carbon (RVC) electrode was studied. The effect of EDTA presence on thecopper electrodeposition process was also evaluated. The electrolytic process took place in anelectrochemical reactor projected with a filter-press configuration, however, with a fewmodifications aiming of a decrease in charge loss. The electrochemical reactor consisted of anRVC porous cathode of 45 ppi and was characterized in terms of mass transfer coefficient(km) which was determined through voltametric and galvanostatic electrodepositiontechniques. In a second phase of this work, the electrodeposition kinetic was studied throughthe application of different current values stipulated as a fraction of the limiting current(α = I / I lim) which was calculated by using km values obtained during the first phase. Thecopper electrodeposition results showed that the voltametric and galvanostatic techniques todetermine km presented very similar values and that the electrodeposition kinetic was nearlyindependent of pH in acid media with pH values between 2 and 4. When it comes to thecopper electrodeposition in EDTA medium, it was observed that the presence of organiccomplexes significantly alter the electrodeposition process and that further phenomena, otherthan mass transfer, control the process. The voltametric technique was not efficient todetermine km values for the zinc electrodeposition and the pH must be controlled with valuesaround 5 in order for galvanostatic electrodeposition to occur. The following correlation formass transfer in the proposed electrochemical reactor was obtained by using the copperelectrodeposition results: Sh = 1.39Re0.57Sc0.33. The comparison of this correlation with that ofother electrochemical reactors cited in the literature showed that it is very efficient when itcomes to mass transfer, and that the presence of the RVC considerably improves theelectrodeposition process. The electrodeposition kinetic results were analyzed in terms ofinstantaneous and global current efficiency and energy consumption efficiencies as a functionof α. It was verified that for Cu2+ and Zn2+ electrodeposition there is an α value whichmaximizes current efficiency and minimizes energy consumption. The optimum α valuedepends on the metal that is being electrodeposited and is lower than 1.0 due to the fact thatthe application of currents lower than the limiting one provides a higher operation time underactivated or mixed control conditions. Finally, it should be observed that the electrodepositionin the presence of EDTA presented an inverse behavior, once the greatest α value studied wasthe one which presented the best results.